Characterization of the cDNA and genomic sequence of a G protein gamma subunit (gamma 5). - Fisher, K J (1992)
A cDNA from human placenta and liver tissues that contained both sequence for the lysosomal glycosidase di-N-acetylchitobiase and sequence homologous to the gamma subunit of GTP-binding proteins was previously isolated. Here we have shown that the gamma-subunit-homologous portion of this unusual cDNA is derived from a member of the gamma-subunit multigene family. The partial human gamma-subunit sequence was used to isolate the corresponding full-length cDNA clones from bovine and rat livers. The two cDNAs encode identical 68-amino-acid proteins (7.3 kDa) homologous to previously cloned G protein gamma subunits. The bovine gene sequence encoding this new gamma-subunit isoform (gamma 5) was determined and found to have an intron-exon structure consistent with the original human chitobiase-gamma 5-subunit hybrid mRNA being a product of alternative splicing. Genomic cloning also resulted in the isolation of a human gamma 5 pseudogene.